Non-neuronal cholinergic stimulation favors bone mass accrual - Tamimi, Faleh; Eimar, Hazem; Alebrahim, Sharifa; Abu-Nada, Lina; Manickam, Garthiga; Al Subaie, Ahmed Ebraheem; Tamimi, Iskandar; Murshed, Monzur (Frontiers in Physiology, 2025)
IntroductionNon-neuronal cholinergic receptors are expressed in immune cells and their stimulation has been shown to regulate the secretion of several cytokines. Some of these cytokines, such as interleukin-17 (IL-17), IL-23, interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α), are known to regulate bone mass. Accordingly, we hypothesize that stimulating cholinergic receptors in non-neuronal cells, such as immune cells, promotes bone mass accrual.MethodsTo test this hypothesis, we used neostigmine, a drug that increases acetylcholine levels by inhibiting acetylcholinesterase activity in peripheral tissues. Female C57BL/6 mice were treated with neostigmine for six weeks, and μCT, histomorphometry, Raman spectroscopy, X-ray diffraction, and mechanical testing were used to analyze bone parameters. A rat model was used to assess bone defect healing and implant osseointegration. Serum cytokines were measured by ELISA, and IL-17 effects on osteoblast proliferation were evaluated in vitro.ResultsHere, we show that 6 weeks of neostigmine treatment promotes bone mass accrual in endochondral bones of both the axial and appendicular skeleton in mice. Moreover, the administration of neostigmine for 2 weeks accelerated the healing process of the surgically induced bone defects in rats. The body mass index, body weight, visceral fat pad weight and epinephrine levels in the neostigmine-treated mice were similar to those of saline-treated mice, indicating that neostigmine favored bone mass accrual by acting peripherally rather than centrally. The increased bone mass in the neostigmine-treated mice was caused by an increase in osteoblast proliferation and bone formation rate. We also observed an increase in circulating immunocytokine IL-17 levels in the neostigmine-treated mice. Statistical analysis showed that the increase in serum IL-17 level was associated with the increase in osteoblast number. In agreement with our findings from the in vivo experiments, IL-17 treatment increased the proliferation of MC3T3.E1 preosteoblasts in vitro, while acetylcholine or neostigmine did not have any significant effect. ConclusionTaken together, our findings indicate that peripheral cholinergic stimulation promotes bone mass accrual, in part through IL-17–mediated osteoblast activity. Although the evidence is correlative, these results highlight a potential neuro-immune pathway and suggest new therapeutic directions for enhancing bone formation and regeneration.